Distributed Diagnostics Tool for Sensor Networks - Xin, Zhang (My University, 2013)
Sensor network plays more and more import role in modern industries, but debugging and diagnosis is always error-prone and time-consuming.This research aims to make up the debugging gap between simulation and testbed on sensor net.‘SUSE’ is a set of tools that provide a variable level debugging and diag-nostics tools on both emulators and testbeds. Firstly, ‘Snapshot collector’ used to generate snapshots on test beds then collect them into a sink node. Secondly ‘Up/Downloader' make helps on transferring data between emu-lators and test beds. 'Standard mask generator' creates variable masks from snapshots. Finally ‘Evaluator’ generates a report depends on comparison between masks that come from emulators and test beds.'SUSE' can fulfill the gap between simulations and testbeds, which also provides help on performing different tests and fault injection on testbeds. 'SUSE' is also a powerful idea that can be expanded to different platforms.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science